Sulfate resistance of alkali-activated slag/Portland cement mortar produced with lightweight pumice aggregate - Dener, Murat; Karatas, Mehmet; Mohabbi, Mehrzad (Elsevier Sci Ltd, 2021)
In this study sulfate resistance of alkali-activated slag/Portland cement mortar produced with lightweight pumice aggregate was investigated. Slag was partly replaced with Portland cement at levels of 0 and 15% by weight. Alkali activator was prepared with a mix of sodium silicate (Na2SiO3) and sodium hydroxide (NaOH). The resistance to sulfate attack was investigated by exposing the mortar samples to 5% magnesium sulfate (MgSO4) and 5% sodium sulfate (Na2SO4) solutions for 1, 3 and 6 months, after which change in compressive strength and mass were determined. Microstructural deteriorations caused by sulfate attack were analyzed by FTIR. Excessive physical deterioration was observed in the mortars immersed in MgSO4 solution, but not in samples immersed in Na2SO4 solution. After all immersion periods in Na2SO4 solution, the compressive strength of both PC-free and 15% PC substituted mortars increased. This increase was higher in PC-free mortars. The compressive strength of mortars immersed in MgSO4 solution started to decrease from the 1st month of exposure.
Keywords: Alkali-activated cement; Portland cement; Slag; Sulfate resistance; Lightweight aggregate